Kinematics and Workspace Analysis of a 1T2R Parallel Mechanism - Jinyue Huang; Guangchun Lin; Hongpeng Quan; Xunbao Liao; Taolue Wang (Jixie chuandong)
A new type of parallel mechanism with 1T2R 3-DOF is proposed， and its kinematics and workspace are analyzed. The characteristics of the mechanism are described in detail， and the degree of freedom is analyzed based on the screw theory， and verified by the modified Grübler-Kutzbach formula. Then， based on the structure and motion characteristics of the mechanism， the forward and inverse kinematics solution model of the mechanism is derived by using the spatial position vector method. The correctness of the model is verified by comparing the theoretical calculation results of a specific example with the simulation results of Adams. The workspace of the parallel mechanism is analyzed based on Monte Carlo method. This study provides a theoretical foundation for the detailed mechanical configuration and practical application of this kind of mechanism.